2021
DOI: 10.7759/cureus.15017
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab-Induced Toxic Epidermal Necrolysis: Rare but Fatal Complication of Immune Checkpoint Inhibitor Therapy

Abstract: Toxic epidermal necrolysis (TEN) is a rare, but potentially fatal dermatological emergency most commonly caused by medication exposure. It is characterized by skin desquamation affecting over 30% of the body, and it remains a fatal condition with a high mortality rate. Nivolumab, an immune checkpoint inhibitor used in the treatment of various types of malignancies, has been linked to TEN. Nivolumab-induced TEN is a rare phenomenon with a low incidence rate in patients treated with a single-agent immune checkpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Table 3 outlines baseline patient characteristics, latency onset, the clinical presentation of SJS/TEN, and outcome and management for each patient. Seven cases were SJS, while TEN was diagnosed in three cases [ 12 , 13 , 15 ], and one case was an SJS/TEN overlap in keeping with our reported patient [ 17 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Table 3 outlines baseline patient characteristics, latency onset, the clinical presentation of SJS/TEN, and outcome and management for each patient. Seven cases were SJS, while TEN was diagnosed in three cases [ 12 , 13 , 15 ], and one case was an SJS/TEN overlap in keeping with our reported patient [ 17 ].…”
Section: Discussionsupporting
confidence: 87%
“…An extensive review published by Maloney et al [4] identified a total of 18 patients with SJS/TEN following treatment with different anti-PD-1 agents (pembrolizumab, ipilimumab, nivolumab, and atezolizumab) [4]. We conducted a comprehensive search to identify nivolumab-induced SJS and/or TEN cases (either as a mono- therapy or combination therapy), which yielded 11 patients [12][13][14][15][16][17][18][19][20][21][22]. One patient was managed with dual therapy with ipilimumab, and one was treated with nivolumab after the failure of ipilimumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 95 cases of ICI‐induced SJS/TEN were identified from 55 peer‐reviewed publications, with 35 cases of SJS, two cases of SJS/TEN overlap, and 26 cases of TEN 7–63 (Figure 1a and Supporting Information Table S1). The precise nomination of the remaining 32 cases as SJS, SJS/TEN overlap or TEN was not specified by authors of the above publications.…”
Section: Resultsmentioning
confidence: 99%